Seismic slope stability analysis using modified pseudo dynamic method with uniform random field of initial phases - Liang Xu; Hongliang Jing; Jiahui Wen; Liang Li; Ziyang Song (PLoS ONE, 2025)
This paper develops an enhanced pseudo dynamic method for conducting seismic stability analysis of slopes. The enhancement is justified by the development of uniform sampling approach and the incorporation of both different and correlated initial phases through a uniform random field. The advanced methodology, named by modified pseudo dynamic Bishop method (MPDBM) is verified against the existing research results and extended to homogeneous soil slope with different scales emphasizing the effect of scale of fluctuation on the minimum factor of safety (FSmin). The numerical results demonstrate that the identical assumption on initial phases in the traditional pseudo dynamic method underestimates the FSmin as compared to the current method considering the spatial variability of initial phases for the cases where the slope soil is subjected to its natural frequency. This underestimation grows significant as the slope scale enlarges.